2020
DOI: 10.14202/vetworld.2020.1430-1438
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, molecular detection, and virulence gene profiles of Campylobacter species in humans and foods of animal origin

Abstract: Background and Aim: Campylobacteriosis is one of the most well-characterized bacterial foodborne infections worldwide that arise chiefly due to the consumption of foods of animal origin such as poultry, milk, and their products. The disease is caused by numerous species within the genus Campylobacter, but Campylobacter jejuni is the most commonly isolated species from established cases of human campylobacteriosis. This study was conducted to determine the prevalence and virulence of Campylobacter isolates from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…A study by Zeinhom et al in 2019 reported a C. jejuni isolation rate of 48% (12/25) from individuals with diarrhea across Beni-Suef Governorate; however, the detection rate was only slightly higher than that from non-diarrheic individuals (32.1%, 9/28) (Zeinhom et al, 2021). Barakat et al reported that 38.1% (40/105) of diarrheic human stools collected in 2018 from five different governorates were PCR positive for Campylobacter, among which a majority of them were C. jejuni(92.5%, 37/40) (Barakat et al, 2020). A similar detection rate of C. jejuni was reported in Sharkia (30%, 30/100) and Ismailia (31.2%, 25/80) Governorates between (Ammar et al, 2020Abdelmageed et al, 2021).…”
Section: Egyptmentioning
confidence: 99%
“…A study by Zeinhom et al in 2019 reported a C. jejuni isolation rate of 48% (12/25) from individuals with diarrhea across Beni-Suef Governorate; however, the detection rate was only slightly higher than that from non-diarrheic individuals (32.1%, 9/28) (Zeinhom et al, 2021). Barakat et al reported that 38.1% (40/105) of diarrheic human stools collected in 2018 from five different governorates were PCR positive for Campylobacter, among which a majority of them were C. jejuni(92.5%, 37/40) (Barakat et al, 2020). A similar detection rate of C. jejuni was reported in Sharkia (30%, 30/100) and Ismailia (31.2%, 25/80) Governorates between (Ammar et al, 2020Abdelmageed et al, 2021).…”
Section: Egyptmentioning
confidence: 99%
“…Also, Barakat et al, [ 40 ] reported that multiplex PCR is a valuable method for detection of virulent and resistant genes of Campylobacter bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…W hile in the present study 12 (63.15%) chicken meat samples were positive on the basis of biochemical testes and 10 (83.33%) by PCR targeting map A gene and hip O genes. Chicken samples were bacteriologically positive for Campylobacter isolates and 285 isolates (94.37%) were identified as C. jejuni by polymerase chain reaction targeting the hip O gene specific for C. jejuni (Barakat et al, 2020).…”
Section: Genotypic Characterizationmentioning
confidence: 99%